Critical Thinking Dispositions of Agricultural Communications Students - Emily Bisdorf-Rhoades; John Ricketts; Tracy Irani; Lisa Lundy; Ricky Telg (Journal of Applied Communications, 2005)
Critical thinking, a reasoned, purposive, and introspective approach to solving problems, has received increased attention from agricultural educators. This study of agricultural communications students utilized a directly administered survey to investigate critical thinking dispositions of agricultural communications students at 12 universities. Results indicated that agricultural communications student respondents tend to be highly innovative in their thinking, an important trait in the field of communications. Results also indicated that few agricultural communication students would be classified as having a strong disposition toward critical thinking, while a larger number would be classified as weak in critical thinking dispositions.